THE REPRESENTATION OF WOMEN’S CHARACTERS IN CINDERELLA THE MOVIE (2015): A FEMINIST ANALYSIS - HERDINDA OCTARI, 121012167 (2017)
Cinderella in Kenneth Branagh movie is seemingly reinvented compared to the cartoon version. Despite admitting that the new Cinderella is rather strong, the findings show otherwise. The women characters found in the movie is shown to be trapped in the negative stereotypes. Cinderella is still passive, the step mother is also very money greedy, the fairy godmother has body dysmorphia, and the step sisters still depend on men. Using narrative and nonnarrative as the method of this study, and feminism as the theory, this research’s result showed that the majority of the female stereotypes found in the original film of Cinderella still existed in the remake in Cinderella 2015 directed by Kenneth Branagh. Thus, even though the media representatives say that stereotypic portrayals have changed over the last few decades, social stereotypes of women still exist today.